The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ecy.2154
|View full text |Cite
|
Sign up to set email alerts
|

Temporal heterogeneity increases with spatial heterogeneity in ecological communities

Abstract: Heterogeneity is increasingly recognized as a foundational characteristic of ecological systems. Under global change, understanding temporal community heterogeneity is necessary for predicting the stability of ecosystem functions and services. Indeed, spatial heterogeneity is commonly used in alternative stable state theory as a predictor of temporal heterogeneity and therefore an early indicator of regime shifts. To evaluate whether spatial heterogeneity in species composition is predictive of temporal hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 65 publications
3
40
0
Order By: Relevance
“…Thus, we created nine simulated communities covering a wide range of species richness and evenness combinations (see Appendix S5 for methods). For each of these nine richness-evenness combinations, we also simulated two well-studied aspects of community variability (Collins et al 2018a) in all possible combinations: (1) spatial variability, a measure of community heterogeneity or beta diversity; and (2) temporal variability, a measure of compositional change over time or turnover. We simulated these aspects of variability using a parameter that controls temporal autocorrelation and one that controls correlation between replicates at each time point (see Appendix S5: Table S1 and Fig.…”
Section: How Are Rac and Multivariate Measures Affected By Species Rimentioning
confidence: 99%
“…Thus, we created nine simulated communities covering a wide range of species richness and evenness combinations (see Appendix S5 for methods). For each of these nine richness-evenness combinations, we also simulated two well-studied aspects of community variability (Collins et al 2018a) in all possible combinations: (1) spatial variability, a measure of community heterogeneity or beta diversity; and (2) temporal variability, a measure of compositional change over time or turnover. We simulated these aspects of variability using a parameter that controls temporal autocorrelation and one that controls correlation between replicates at each time point (see Appendix S5: Table S1 and Fig.…”
Section: How Are Rac and Multivariate Measures Affected By Species Rimentioning
confidence: 99%
“…Thus, differences in the magnitude of the biodiversity response between studies, systems, or organism groups might not only reflect differing impacts of drivers, but also varying abilities to respond due to the spatial species distribution of the surroundings (Collins et al . ). This makes direct comparison of compositional responses to environmental change difficult.…”
Section: Introductionmentioning
confidence: 97%
“…Compositional responses to changing environmental conditions might be limited if low beta diversity reduces rates of immigration and consequently constrains temporal turnover. Thus, differences in the magnitude of the biodiversity response between studies, systems, or organism groups might not only reflect differing impacts of drivers, but also varying abilities to respond due to the spatial species distribution of the surroundings (Collins et al 2018). This makes direct comparison of compositional responses to environmental change difficult.…”
Section: Introductionmentioning
confidence: 99%
“…As the samples were repeatedly collected from each site over two years, we also included temporal scale in our analyses to evaluate community shifts related to seasonality and succession that might potentially interfere with spatial distribution or species sorting by local conditions. Temporal effects are usually neglected in metacommunity studies focused on lentic ecosystems, although they were found to substantially affect metacommunity structure across various types of localities and studies (Collins et al., ), as those of lotic habitats (Erős, Sály, Takács, Specziár, & Bíró, ; Sarremejane et al., ), floodplains (Fernandes, Henriques‐Silva, Penha, Zuanon, & Peres‐Neto, ), dynamic experimental mesocosms (Azeria & Kolasa, ), as well as in studies in terrestrial environments, e.g., on plants (Alexander et al., ) and mammals (Delciellos et al., ).…”
Section: Introductionmentioning
confidence: 99%